ZIONISME DAN BERDIRINYA NEGARA ISRAEL - Saude, Saude (Institut Agama Islam Negeri (IAIN) Palu, 2006)
Zionism is a political movement established on Judism doctrines. The very prominent mission of this movement is to establish an independent state of Israel. The Jews claim themselves to be the choosen people. In addition, they claim that Israel is the holy land promised by God. Therefore, they keep on fighting the Palestinians for the promised holy land. Kata Kunci: Zionisme, Yahudi, Israel